Evidence of a functional reorganization in the auditory dorsal stream following unilateral hearing loss. (December 2020) - Vannson, Nicolas; Strelnikov, Kuzma; James, Chris J.; Deguine, Olivier; Barone, Pascal; Marx, Mathieu
Abstract: Unilateral hearing loss (UHL) generates a disruption of binaural hearing mechanisms, which impairs sound localization and speech understanding in noisy environments. We conducted an original study using fMRI and psychoacoustic assessments to investigate the relationships between the extent of cortical reorganization across the auditory areas for UHL patients, the severity of unilateral hearing loss, and the deficit in binaural abilities. Twenty-eight volunteers (14 UHL patients) were recruited (twenty-two females and six males). The brain imaging analysis demonstrated that UHL induces a shift in aural dominance favoring the better ear, with a cortical reorganization located in the non-primary auditory areas, ipsilateral (same side) to the better ear. This reorganization is correlated not only to the hearing loss severity but also to spatial localization abilities. A regression analysis between brain activity and patient's performance clearly showed that the spatial hearing deficit was linked to a functional alteration of the posterior auditory areas known to process spatial hearing. Altogether, our study reveals that UHL alters the dorsal auditory stream, which is deleterious to spatial hearing. Highlights: Acquired unilateral hearing loss induces a shift in aural preference in favor of the hemisphere ipsilateral to the better ear. This hemisphere asymmetry shift is observed in the non-primary auditory cortex (NPAC) We found a significant correlation between localization ability and brain reorganization of the NPAC. It indicates that the lower the brain reorganization, the higher localization capability.